Dynamics of HSV-2 infection with a therapeutic vaccine - Ezio Venturino; Affan Shoukat; Seyed M. Moghadas (Heliyon, 2020)
Herpes-Simplex Virus type 2 (HSV-2) is a lifelong infection, which has infected over 400 million individuals aged 15-49 years, worldwide. While the disease can be treated with episodic and suppressive antiviral drugs to reduce the rate of recurrence (i.e., symptomatic disease) and viral shedding, none of the currently available therapies can clear the virus from the body of an infected person. A number of therapeutic vaccine platforms are currently in development in order to achieve similar effects to treatment. Due to the inadequate data from clinical trials of therapeutic vaccines, modeling efforts to quantify the impact of vaccination have been limited. In this study, we propose a compartmental deterministic model for the dynamics of HSV-2 to evaluate the effect of a potential vaccine candidate with the inclusion of a booster dose. Despite its simplicity that may not address the complexity of HSV-2 disease, the model shows that targeting symptomatic infection for vaccination is the most effective strategy in the long-term. This conclusion is based on the assumption of an optimal vaccine efficacy, conferring immunity levels that prevent viral shedding and recurrence transiently. Our model provides a framework for developing a computational system to include more heterogeneous characteristics of the disease and individuals, and investigate effectiveness and cost-effectiveness of vaccination scenarios when clinical data become available.